A domino-like localized cascade toehold assembly amplification-based DNA nanowire for microRNA imaging in living cells. Issue 48 (30th November 2022) - Yang, Zizhong; Liu, Birong; Huang, Ting; Sun, Mengxu; Tong li,; Duan, Wen-Jun; Li, Min-Min; Chen, Jin-Xiang; Dai, Zong; Chen, Jun
Abstract : A domino-like localized cascade toehold assembly amplification-based DNA nanowire was proposed for microRNA imaging in living cells. Abstract : High sensitivity and specificity imaging of miRNA in living cells plays an important role in understanding miRNA-related regulation and pathological research. Localized DNA circuits have shown good performance in reaction rate and sensitivity and have been proposed for sensitive imaging of miRNA in living cells. However, most reported localized DNA circuits have a high risk of derailment or a limited loading rate capacity, which hinder their further application. To solve these issues, we herein developed a domino-like localized cascade toehold assembly (LCTA) amplification-based DNA nanowire to achieve highly sensitive and highly specific imaging of miRNAs in living cells by using DNA nanowires as reactant delivery vehicles and confining both reactant probes in a compact space. The LCTA is constructed by interval hybridization of DNA double-stranded probe pairs to a DNA nanowire with multiplex footholds generated by alternating chain hybridization. Due to the localized effect, the LCTA showed high reaction kinetics and sensitivity, and the method could detect miRNAs as low as 51 pM. The LCTA was proven to be able to accurately distinguish the miRNA expression difference between normal cells and cancer cells. In particular, the developed LCTA could be used to construct an OR logic gate to simultaneously image the total amount of multiple miRNAs in living cells. We believe that the developed LCTA can be an effective intracellular nucleic acid imaging tool and can promote the development of nucleic acid-related clinical disease diagnosis and DNA logical sensors.